Validation of an electrothermal atomization atomic absorption spectrometry method for quantification of total Chromium and Chromium(VI) in wild mushrooms and underlying soils - Figueiredo, Ana E. (2008)
An ETAAS method was validated to quantify total Cr and CrVI in mushrooms and the underlying soils. The method includes a sample pretreatment for total Cr dissolution using a wet acid digestion procedure and a selective alkaline extraction for CrVI. The limits of detection were, expressed in íg/L, 0.15 and 0.17 for total Cr and CrVI, respectively. The linearity ranges under the optimized conditions were 0.15-25.0 and 0.17-20.0 íg/L for total Cr and CrVI, respectively. The limits of quantification were, expressed in íg/g of dry weight, 0.0163 and 0.0085 for total and hexavalent chromium, respectively. The precision of the instrumental method for total Cr and CrVI was lower than 1.6%, and for the analytical method, it was lower than 10%. The accuracy of the method for CrVI quantification was evaluated by the standard additions method, with the recoveries being higher than 90% for all of the added concentrations. For total Cr, certified reference materials (lichen CRM 482 and soil sample NCS ZC73001) were used. An interference study was also carried out in a mushroom simulated matrix, and it was verified that the deviations of the expected values were lower than 4.0% for both total Cr and CrVI. The validated method was applied to the evaluation of total Cr and CrVI in 34 wild mushrooms and 34 respective underlying soil samples collected in two different regions of Portugal (Beira Interior and Trás-os-Montes), with different locations regarded as noncontaminated or contaminated areas. The species were identified by a mycologist and subdivided into 10 genera and 15 species: Amanita ( rubescens, muscaria, and ponderosa), Boletus ( regius), Lactarius( deliciosus, vellereus, and piperatus), Suillus( granulatusand luteus), Tricholoma( acerbum), Agaricus( sylvicola), Volvariella( gloiocephala), Lecopaxillus( giganteus), Macrolepiota( procera), and Psilocybe( fascicularis). The mean values found for total Cr were 1.14 and 1.11 íg/g of dry weight, and for CrVI, the mean values were 0.103 and 0.143 íg/g of dry weight for cap and stalk, respectively. For soils, the mean concentrations found were, for total Cr, 84.0 íg/g and, for CrVI, 0.483 íg/g. The bioconcentration factors (BCFs) based on dry weight for cap and stalk were determined, and the values found, for both total Cr and CrVI, were always <1, although for hexavalent chromium, the BCFs were 10 times higher than for total chromium.